Survey on the level of physical fitness of female students aged 13-15 years - Sonia Raihanah; Ruruh Andayani Bekti; Budiman Agung Pratama (Sriwijaya Journal of Sport, 2022)
The purpose of the study was to determine the level of fitness of class VIII female students. The research approach used is quantitative descriptive research through observation or tests. The subjects in this study were female students of class VIII at Darul Hikmah Islamic Boarding School, Tulungagung Regency, which consisted of 16 female students. In this study, the subject selection technique used purposive sampling technique, namely the subject selection technique determined by the researcher himself. Data collection techniques using surveys with test and measurement techniques. The instrument used is the Indonesian Physical Fitness Test (IPFT) for 13-15-year-olds. Based on the IPFT, Santriwati test score data that most of the students in the poor category with total scores between 10-13 as many as 10 students (62.5%) and a small number of students in the very poor category with a total score between 5-9 as many as 2 students (12,5%) and the poor category with a total score between 14-17 in the medium category. Thus, the results of the physical fitneess test scores on female students are mostly in the poor category.